Knowledge in digital environments: A systematic review of literature - Platonova, Raisa I.; Khuziakhmetov, Anvar N.; Prokopyev, Alexey I.; Rastorgueva, Natalia E.; Rushina, Marina A.; Chistyakov, Alexey A. (Frontiers in Education, 2022)
There are several meanings of the term “knowledge” that match to the diverse study areas. A knowledge creation, sharing, dissemination, and presentation environment is required. Digital platforms and technology lead to the development of innovative methods of teaching and learning in a digital environment. It is of intellectual and academic interest to determine if knowledge processes change in digital contexts, which provide more options than conventional environments such as books and newspapers. The study is built on an exhaustive examination of prior studies on knowledge in digital contexts. The databases ERIC and Scopus served as the search grounds for the keyword-based inquiry. The collected documents were evaluated to determine whether or not they contributed to the investigation's objective. The cornerstone of our inquiry was a careful review of the remaining 14 studies. For quantitative investigations, the experimental design was the most desired approach, but the case study method was the most preferred method for qualitative research. The objectives of the research employ the terms “knowledge” and “digital environments” either directly or implicitly. Studies were designated as “creating” “creating with cooperation” “acquiring” “presenting” and “sharing” In the research, data was coded in accordance with the responsibilities assigned in digital worlds. In the study, 10 distinct theories and models were referenced. These models and hypotheses are categorized based such as creating, acquiring, designing, and using their interaction with data. In the investigations, the existence of traditional knowledge creation and application has been investigated. In addition, the process's distinction owing to the capabilities of digital environments has been investigated.